1998
DOI: 10.1037/0022-3514.75.2.347
|View full text |Cite
|
Sign up to set email alerts
|

Pragmatic use of categorical information in impression formation.

Abstract: We thank Norbert Schneider and Martina Schradi for their help in collecting the present data and Paul Cash for his help with language problems. We also thank Guido Gendolla and Waldemar Lilli for helpful comments on an earlier version of this article.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(8 citation statements)
references
References 59 publications
(91 reference statements)
0
8
0
Order By: Relevance
“…For example, when asked to judge the size of ambiguous animals, people assimilate to the size of the animals previously presented to them (the primes) if they are moderately small (e.g., cat) or moderately large (e.g., cow). However, people exhibit contrast effects if the previously presented animal is extremely large (e.g., whale) or extremely small (e.g., flea) (Abele & Petzold, 1998;Herr, 1986;Herr, Sherman, & Fazio, 1983;Montgomery, 1980;Mussweiler & Strack, 2000). Contrast effects also take place when the primes are seen as incongruent or disassociated with the perceiver's self-concept (Koole, Dijksterhuis, & Van Knippenberg, 2001;Spears, Gordijn, Dijksterhuis, & Stapel, 2004;Stapel & Koomen, 2000Staple & Blanton, 2004).…”
Section: Contrast Effects Of Low Biismentioning
confidence: 99%
“…For example, when asked to judge the size of ambiguous animals, people assimilate to the size of the animals previously presented to them (the primes) if they are moderately small (e.g., cat) or moderately large (e.g., cow). However, people exhibit contrast effects if the previously presented animal is extremely large (e.g., whale) or extremely small (e.g., flea) (Abele & Petzold, 1998;Herr, 1986;Herr, Sherman, & Fazio, 1983;Montgomery, 1980;Mussweiler & Strack, 2000). Contrast effects also take place when the primes are seen as incongruent or disassociated with the perceiver's self-concept (Koole, Dijksterhuis, & Van Knippenberg, 2001;Spears, Gordijn, Dijksterhuis, & Stapel, 2004;Stapel & Koomen, 2000Staple & Blanton, 2004).…”
Section: Contrast Effects Of Low Biismentioning
confidence: 99%
“…They argued that participants try to determine the meaning of the task not because they want to behave as a 'good participant' (Orne, 1962), but rather because they follow the conversational rules of being informative, relevant, truthful and unambiguous (Grice, 1975). Abele and Petzold (1998) showed that participants try to use all information presented by making sense of both explicit information and subtle cues ('meta-information') in the task.…”
mentioning
confidence: 99%
“…Note that the task's objective does not necessarily need to be explicitly stated (e.g., Trope & Lieberman, 2000), but can be inferred by meta-informational cues such as the format in which information is presented (Abele & Petzold, 1998). When individuals infer the task to be one of discrimination between categories, for example, category information is weighted more heavily and evaluations of individual category members are assimilated to the category average.…”
Section: Evaluation Tasksmentioning
confidence: 98%
“…As such, these results are not merely methodological artifacts, but are in fact theoretically informative. The overall theoretical perspective we apply to this question is based on prior research that, in other contexts, has shown that the evaluation task decision makers face determines which pieces of information seem more task relevant and thus are weighted more heavily (e.g., Abele & Petzold, 1998;Fischer, Carmon, Ariely, & Zauberman, 1999;Mussweiler 2003;Trope & Lieberman, 2000).…”
mentioning
confidence: 99%